Spermatogenesis : biology and clinical implications - Cheng, C. Yan (Boca Raton, FL : CRC Press, 2019)
Senior investigators internationally have here collaborated to produce an international reference work. Each contributor provides critical and thought provoking concepts and ideas based on the latest developments in their field. The result is a must read and timely reference work for investigators who are interested in how spermatogenesis is currently understood and which are the most promising avenues for future research; an Introduction sets the context for the chapter and points out the relevance of the research for basic research scientists and clinicians.
OCLC-licensed vendor bibliographic record.
Keywords: Spermatogenesis; SCIENCE / Life Sciences / Anatomy & Physiology; MEDICAL / Anatomy; MEDICAL / Reproductive Medicine & Technology; MEDICAL / Urology